1983
DOI: 10.1111/j.1432-1033.1983.tb07588.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Cadmium Binding to Troponin C

Abstract: Proton NMR is used to compare the structural changes induced in bovine cardiac troponin C on binding of cadmium and calcium ions. The same spectral changes are observed for both ion species. The rate of the conformational changes associated with cadmium binding to the two high‐affinity sites is slow, that associated with cadmium ions binding to the low‐affinity site is high. 113Cd‐NMR spectra of cardiac troponin C feature two signals interpreted as due to cadmium ions bound to the strong sites. Strong argumen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Previous studies on Ca 2+ binding to troponin C by Ca 2+ titration ( 36, 37, 52, 53, 64 ) indicated the binding is cooperative and affected by pH. Those studies, however, did not give a clear outcome of the binding order of Ca 2+ to troponin C probably because the similar binding affinities of Ca 2+ in each terminal region of troponin C cause the states to coexist at various Ca 2+ concentrations.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies on Ca 2+ binding to troponin C by Ca 2+ titration ( 36, 37, 52, 53, 64 ) indicated the binding is cooperative and affected by pH. Those studies, however, did not give a clear outcome of the binding order of Ca 2+ to troponin C probably because the similar binding affinities of Ca 2+ in each terminal region of troponin C cause the states to coexist at various Ca 2+ concentrations.…”
Section: Discussionmentioning
confidence: 95%
“…Guided by the fractional species calculation, the deuterium patterns for each EF-hand were measured as a function of the various Ca 2+ binding states (i.e., 0, 1, 2, 3, and 4) to determine how D distributions change as a function of the binding states. Previous efforts to elucidate the binding properties of Ca 2+ to troponin C used NMR, fluorescence measurement, Ca 2+ ion-selective electrode measurements, and mutagenesis ( 36, 37, 52, 53 ). Although some insights were achieved, a full understanding on the Ca 2+ binding order is still lacking.…”
mentioning
confidence: 99%
“…The pathophysiology of these phenomena is not well established but a number of publications have suggested potential mechanisms; e.g. oxidative damage to the heart by an alteration of anti-oxidant defence and an increased generation of ROS (Jamall et al 1989;Zikic et al 1998;Wang et al 2004), a reduction in coronary blood flow in isolated heart studies by Cd (Kisling et al 1993), an inhibition of cardiomyocyte electron transfer chain by Cd (Wang et al 2004), as well as a direct interactions of Cd with troponin C (Teleman et al 1983) and myoglobin (Lepeshkevich and Dzhagarov 2009). Effects on the cardiac conduction system are based on interactions of Cd with contraction and pacing systems.…”
Section: Cadmium and The Heartmentioning
confidence: 99%
“…This latter model is supported by kinetic and conformational studies. In fact, based on 43Ca2+-NMR [372] and stopped-flow fast kinetics [373], it has been shown that the N-terminal half of calmodulin has a k,ff of 300-500 s-' while the C-terminus has a koff of 10 -40 s-'. Assuming a diffusion controlled on-rate constant, these data suggest the existence of high-affinity sites in the C-terminus and low-affinity sites in the N-terminus of the protein.…”
Section: The Cu2mentioning
confidence: 99%